Acetaminophen poisonings hospitalized at the Pomeranian Center of Toxicology in 2010−2015 - Bartłomiej Garczewski; Marek Wiśniewski; Wojciech Waldman; Jacek Sein Anand (Nofer Institute of Occupational Medicine, 2019)
Background Acetaminophen is a widely available analgesic and antipyretic medication. Although it is advertised as safe, it is responsible for more than 50% of drug-induced hepatotoxicity cases and the most common cause of acute liver failure in developed countries. Until 2000 the frequency of acetaminophen overdoses in Poland was relatively low, but a significant increase has been seen in recent years. The aim of the study was to perform a demographic analysis of the acetaminophen overdose cases hospitalized at the Pomeranian Center of Toxicology (PCT) in Gdańsk, Poland, in 2010-2015. Material and Methods The Pomeranian Center of Toxicology in Gdańsk is the Regional Clinical Toxicology Center for a population of more than 3.5 million people from the Pomeranian and the Warmian-Masurian Voivodeships. All the patients hospitalized at PCT in 2010-2015 were analyzed. Cases in which the primary or secondary diagnosis was encoded as T39.1, according to the International Classification of Diseases ICD-10, were selected. Statistical analysis was performed using the χ 2 and McNemara tests. Results In the reference period, 7754 poisoned patients were hospitalized, including 4163 men and 3591 women. There were 667 cases of acetaminophen overdose (231 men and 436 women). There was a significant increase in the percentage of acetaminophen overdoses in 2010-2015 (6.5% and 10.8%, p < 0.01). In the group aged < 18 years, there were 217 cases of acetaminophen overdose (37 men and 180 women). The share or acetaminophen overdose cases in this group (17.2%) was significantly higher than among patients aged ≥ 18 years (6.9%, p < 0.01). The male to female ratio in the group aged ≥ 18 years was 0.75, and in the group aged < 18 years it was 0.21 (p < 0.01). Conclusions There was a significant increase in the number of acetaminophen overdose cases hospitalized at the Pomeranian Center of Toxicology in 2010-2015. The share of acetaminophen overdoses was significantly higher in the group aged < 18 years than in the adult group. In both age groups, acetaminophen overdose was more frequent in women. Med Pr. 2019;70(6):733-8